2013
DOI: 10.1111/tpj.12334
|View full text |Cite|
|
Sign up to set email alerts
|

ABCG9, ABCG11 and ABCG14 ABC transporters are required for vascular development in Arabidopsis

Abstract: SUMMARYIn order to obtain insights into the regulatory pathways controlling phloem development, we characterized three genes encoding membrane proteins from the G sub-family of ABC transporters (ABCG9, ABCG11 and ABCG14), whose expression in the phloem has been confirmed. Mutations in the genes encoding these dimerizing 'half transporters' are semi-dominant and result in vascular patterning defects in cotyledons and the floral stem. Co-immunoprecipitation and bimolecular fluorescence complementation experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 57 publications
(107 reference statements)
1
34
0
2
Order By: Relevance
“…Because homo- and heterodimers of ABCG11 and ABCG12 are reported as important for wax export and ABCG13 seems to be required for cutin deposition in flowers [ 67 ], it is widely accepted that tissue-dependent combinations of different half-size ABCG proteins involved in the transport of wax, cutin and suberin components are possible to occur [ 61 ]. Furthermore, ABCG11 can form dimers with ABCG9 and ABCG14 which links it to a function in lipid homeostasis regulation in vascular organs as phloem [ 68 ]. Additionally, a recent study reported that half-size ABCG2, ABCG6 and ABCG20 are involved in the formation of suberin layers in seed coats and roots where abcg2/6/20 triple mutants had increased permeability, altered suberin structure and reduce aliphatic components [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because homo- and heterodimers of ABCG11 and ABCG12 are reported as important for wax export and ABCG13 seems to be required for cutin deposition in flowers [ 67 ], it is widely accepted that tissue-dependent combinations of different half-size ABCG proteins involved in the transport of wax, cutin and suberin components are possible to occur [ 61 ]. Furthermore, ABCG11 can form dimers with ABCG9 and ABCG14 which links it to a function in lipid homeostasis regulation in vascular organs as phloem [ 68 ]. Additionally, a recent study reported that half-size ABCG2, ABCG6 and ABCG20 are involved in the formation of suberin layers in seed coats and roots where abcg2/6/20 triple mutants had increased permeability, altered suberin structure and reduce aliphatic components [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. thaliana AtABCG25 and AtABCG40 are involved in abscisic acid (ABA) transport and responses [ 68 , 69 ]. Recent studies have indicated that ABCG9, ABCG11 and ABCG14 are involved in lipid/sterol homeostasis regulation, which is required for proper vascular development in A. thaliana [ 70 ]. Finally, some members of ABCG subfamily confer plant resistance to various biotic and abiotic stresses [ 71 , 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in animal system a co-regulation of fatty acid production and sterol biosynthesis is observed for proper maintenance of cell membranes during cellular growth [ 55 , 56 ]. Studies in Arabidopsis sterol biosynthetic mutants have also revealed changes in fatty acid composition indicating a link between sterol and fatty acid metabolism [ 57 , 58 , 59 ]. The changes in fatty acid esters is solely due to increase in flux into fatty acid biosynthesis upon monoterpene pathway inhibition or increase in sterols also has an impact on FA metabolism remains to be deciphered.…”
Section: Discussionmentioning
confidence: 99%